Exploring the responsiveness and quality of email responses from hotels in North America, South America and the Caribbean: A linguistic approach - Simons, Z (2011)
This study explores the influence that language has on the responsiveness and quality of email responses to customer inquires sent to hotels in North America, South America and the Caribbean. Observing language as both a characteristic and variable, it is explored holistically. Previous studies have indicated that although there is adequate responsiveness, quality has been relatively poor. Thus, the study first looks to confirm the conclusions drawn by past studies using Chi-square analysis and Kruskal-Wallis tests. It conducts further analysis to explore the differences between the languages used, English and Spanish. In addition, this study explores the relationship between the variables and overall customer rating. Chi-square results reveal that hotel characteristics and language do not influence the responsiveness, quality or linguistics variables used. Kruskal-Wallis results show few differences between North America and the other locations. Standard multiple regression results show that there are no strong correlations between the variables and overall customer relationship. Email inquires serve as a form of customer service. It is important for managers to recognize the service of email and its implementation, applying it appropriately to their strategies in order to create competitive advantage.